Immunogenicity assessment of elder hepatocellular carcinoma patients after inactivated whole-virion SARS-CoV-2 vaccination - Ruyun Gao; Cuiling Zheng; Mengwei Yang; Liyuan Dai; Chen Chen; Jiarui Yao; Zhishang Zhang; Le Tang; Yuankai Shi; Xiaohong Han (Taylor & Francis Group, 2023)
Background Research on immunogenicity after 3rd SARS-CoV-2 vaccine in elder hepatocellular carcinoma (HCC) was limited. This study aimed to investigate the efficacy and influencing factors of inactivated SARS-CoV-2 vaccine in elder HCC. Research design and methods We assessed total antibodies, anti-RBD IgG, and neutralizing antibodies (NAb) toward SARS-CoV-2 wild type (WT) as well as BA.4/5 in 304 uninfected HCC, 147 matched healthy control (HC), and 53 SARS-CoV-2 infected HCC, all aged over 60 years. The levels of antibodies were compared in the period 7-90, 91-180, and >180 days after 2nd or 3rd vaccination, respectively. Results HCC had lower seropositivity than HC after 2nd dose (total antibodies, 64%vs.92%,P < 0.0001; anti-RBD IgG, 50%vs.77%,P < 0.0001). But 3rd dose can efficaciously close the gap (total antibodies, 96%vs.100%,P = 0.1212; anti-RBD IgG: 87%vs.87%,P > 0.9999). Booster effect of 3rd dose can persist >180 days in HCC (2ndvs.3rd: total antibodies, 0.60vs.3.20,P < 0.0001; anti-RBD IgG, 13.86vs.68.85,P < 0.0001; WT NAb, 11.70vs.22.47,P < 0.0001). Vaccinated HCC had more evident humoral responses than unvaccinated ones after infection (total antibodies: 3.85vs.3.20,P < 0.0001; anti-RBD IgG: 910.92vs.68.85,P < 0.0001; WT NAb: 96.09vs.22.47,P < 0.0001; BA.4/5 NAb: 86.53vs.5.59,P < 0.0001). Conclusions Our findings highlight the booster effect and protective role of 3rd dose. Our results could provide a theoretical foundation for informing decisions regarding SARS-CoV-2 vaccination in elder HCC.